2023
DOI: 10.1186/s12864-023-09200-z
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional profiling of Xanthomonas campestris pv. campestris in viable but nonculturable state

Abstract: Background Xanthomonas campestris pv. campestris (Xcc) is an important seed-borne plant pathogenic bacteria that can cause a serious threat to cruciferous crops. Bacteria can enter into the viable but non-culturable (VBNC) state under stress conditions, and cause potential risks to agricultural production because the VBNC bacterial cells will evade culture-based detection. However, little is known about the mechanism of VBNC. Our previous study showed that Xcc could be induced into VBNC state b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…In recent metabolomics studies of the VBNC state, it has been observed in various bacterial species that active metabolic pathways are linked to the transport and metabolism of inorganic ions, carbohydrates, and amino acids, as well as pathways involved in the synthesis of the cell wall, membrane, and envelope [ 128 ]. Additionally, it has been determined that during the VBNC state, there is an augmentation in the amino acid content, consequently leading to the alteration of specific amino acid metabolic pathways, such as the biosynthesis of aminoacyl-tRNA and the metabolism of arginine, proline, alanine, aspartate, and glutamate.…”
Section: Proteomics Transcriptomics and Metabolomics Of Bacterial Cel...mentioning
confidence: 99%
“…In recent metabolomics studies of the VBNC state, it has been observed in various bacterial species that active metabolic pathways are linked to the transport and metabolism of inorganic ions, carbohydrates, and amino acids, as well as pathways involved in the synthesis of the cell wall, membrane, and envelope [ 128 ]. Additionally, it has been determined that during the VBNC state, there is an augmentation in the amino acid content, consequently leading to the alteration of specific amino acid metabolic pathways, such as the biosynthesis of aminoacyl-tRNA and the metabolism of arginine, proline, alanine, aspartate, and glutamate.…”
Section: Proteomics Transcriptomics and Metabolomics Of Bacterial Cel...mentioning
confidence: 99%